Trends in the global burden of gout attributable to kidney dysfunction, 1990-2021: a population-based analysis - Xu, Jiaxian; Lei, Mingming; Xu, Dandan (Frontiers in Endocrinology, 2025)
BackgroundGout, primarily driven by hyperuricemia, is a prevalent inflammatory arthritis with kidney dysfunction being a significant risk factor. This study aims to comprehensively evaluate the global burden of gout attributable to kidney dysfunction from 1990 to 2021, highlighting differences across regions, genders, Socio-Demographic Index (SDI) levels, and age groups.MethodsUsing data from the Global Burden of Disease (GBD) 2021 study, we assessed the burden of gout due to kidney dysfunction using disability-adjusted life years (DALYs) and years lived with disability (YLDs). Kidney dysfunction was defined as an estimated glomerular filtration rate (eGFR) below 60 mL/min/1.73 m² or an albumin-to-creatinine ratio (ACR) ≥30 mg/g. The data were stratified by region, country, gender, age, and SDI quintiles. The annual percentage change (EAPC) was calculated to determine temporal trends.ResultsFrom 1990 to 2021, global DALYs and YLDs attributable to gout due to kidney dysfunction increased significantly, rising from 78,564.8 years (95% uncertainty interval 48,687.9–118,061.9) to 200,033.3 years (125,245.0–296,812.4), a 2.5-fold increase. The age-standardized DALY rate (ASDR) and age-standardized YLD rate both increased, from 2.1 per 100,000 population in 1990 to 2.4 per 100,000 in 2021. DALY and YLD rates were consistently higher in males than in females. High SDI countries, especially North America and Australasia, had the most significant rise in burden, whereas low SDI regions experienced a decline. The burden increased with age, particularly in those aged 60 and above.InterpretationThis study underscores the substantial increase in the global burden of gout attributable to kidney dysfunction, particularly among the elderly, males, and populations in high SDI regions. The observed trends are driven by multiple factors, including lifestyle and dietary habits, diagnostic capacity, and demographic shifts. Future efforts should focus on improving surveillance and access to care in low-SDI regions to address potential underestimation of the burden. High-SDI regions should prioritize personalized health management strategies for the elderly, emphasizing early detection and intervention for gout and kidney dysfunction.